Sensorial properties of red wine polyphenols: Astringency and bitterness - Soares, Susana; Brandão, Elsa; Mateus, Nuno; de Freitas, Victor (Critical reviews in food science and nutrition, 2017)
Polyphenols have been the subject of numerous research over the past years, being referred as the nutraceuticals of modern life. The healthy properties of these compounds have been associated to a natural chemoprevention of 21st century major diseases such as cancer and neurodegenerative diseases (e.g. Parkinson's and Alzheimer's). This association led to an increased consumption of foodstuffs rich in these compounds such as red wine. Related to the ingestion of polyphenols are the herein revised sensorial properties (astringency and bitterness) which are not still pleasant. This review intends to be an outline both at a sensory as a molecular level of the mechanisms underlying astringency and bitterness of polyphenols. Up-to-date knowledge of this matter is discussed in detail.